Anchor and hope [videorecording (DVD)] - Marques-Marcet, Carlos, 1983-; Chaplin, Oona, 1986-; Tena, Natalia, 1984-; Verdaguer, David, 1983-; Chaplin, Geraldine, 1944- (Wolfe Video, 2018)
In their mid-30s, Eva and Kat have a fun and carefree simple life in their London canal boat until Eva, inspired by her exceptional mother Germaine (played by her real mother Geraldine Chaplin), presents Kat with an ultimatum: she wants a child. Kat resists, knowing that it will end the bohemian lifestyle that she's always envisioned with Eva. When Kat's best friend, Roger, drops in from Barcelona, the three of them toy around with the idea of creating a baby together.